Copolymer, preparation method and application thereof, and clay stabilizer
By developing a copolymer containing multiple amine groups and N+ groups as clay stabilizers, the problem of clay stabilizers in the prior art is easily blocked and poor compatibility in low permeability reservoirs, and good temperature resistance, anti-swelling performance and water washing resistance are achieved.
Patent Information
- Application Number
- CN202311401210.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
Existing clay stabilizers are prone to block the pores in low-permeability reservoirs, and their positive charge content is poor in compatibility with the anionic surfactants, anionic polymers and acidified fracturing fluids used in the oil dispersion process.
A copolymer is developed whose structure contains multiple amine groups and N+ groups, which can form multi-point adsorption and be well compatible with anionic polymer. The preparation method includes polymerization of polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride in the presence of water and an initiator.
The multi-point adsorption and good compatibility of clay stabilizers are achieved, and they have excellent temperature resistance, anti-swelling properties and water washing resistance. At the same time, the molecular weight is moderate and it is not easy to block low-permeability channels.
Smart Images

Figure BDA0004515328620000031 
Figure BDA0004515328620000051 
Figure BDA0004515328620000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil production engineering, and in particular to a copolymer, a preparation method and application thereof, and a clay stabilizer. Background Art
[0002] In the process of oil extraction, water injection is usually used to maintain formation pressure. After water is injected into the oil and gas layer, water comes into contact with clay minerals in the formation, causing the clay minerals to hydrate, swell, disperse and migrate, thereby blocking the throat of the formation void structure, resulting in a decrease in formation permeability and formation damage. During the expansion process, clay absorbs water into the crystal structure, causing its volume to increase, thereby blocking the formation pores; during the migration process, clay minerals will be dispersed by foreign liquids or carried by produced liquids, so that bridge resistance or throttling points are formed at the throat of the voids, thereby reducing the permeability of the formation. After the formation permeability decreases, the water injection pressure increases rapidly, water injection becomes difficult, and even water injection cannot be performed, thereby reducing the water drive effect, and further affecting the crude oil production and the recovery rate of the oil field. For this type of reservoir with high clay mineral content and strong water sensitivity, water-sensitive damage may be caused as long as water-based working fluid is injected during drilling, completion, perforation, acidification, fracturing, water injection, oil production, and enhanced oil recovery. Therefore, for this type of potential damage in reservoir clay minerals, an effective method is to inject clay stabilizers for front edge protection before water injection or water transfer.
[0003] Clay stabilizers can be divided into four categories according to their chemical composition, namely inorganic salts and inorganic bases, inorganic polymers, cationic surfactants and organic cationic polymers. Currently, the most widely used are polyquaternary ammonium clay stabilizers of the organic cationic polymer type. Although polyquaternary ammonium clay stabilizers have good anti-swelling properties, they have two disadvantages: (1) polyquaternary ammonium clay stabilizers have a large molecular weight and are not suitable for low permeability reservoirs; (2) the molecular chain carries a large amount of positive charges and has poor compatibility with anionic polymers.
[0004] CN115232016A discloses a clay stabilizer solution and a preparation method thereof. The clay stabilizer is prepared by a tertiary amination reaction of dimethylamine and benzyl chloride to prepare an N,N-dimethylaniline intermediate, which is then quaternized with epoxypropyltrimethylammonium chloride. The clay stabilizer has two N+ and can adsorb clay at the same time, and has a certain anti-swelling effect. However, the clay stabilizer has not only few adsorption sites, but also a high positive charge content, and poor compatibility with anionic surfactants, anionic polymers and acid fracturing fluids used in the oil displacement process.
[0005] CN116120547A discloses a clay stabilizer and a preparation method thereof. The main chain of the clay stabilizer contains a large number of quaternary ammonium salt cations and a large number of positive charges. The clay stabilizer can be adsorbed with multiple clay particles at the same time to form multi-point adsorption, thereby inhibiting the hydration expansion of the clay. The clay stabilizer has a large degree of freedom of movement and has a strong control effect on the dispersion and migration of clay particles. The clay stabilizer has strong water washability and can form a dense hydration film on the surface of the clay particles, thereby preventing and delaying the contact between water molecules and the clay surface, thereby preventing the hydration expansion of the clay. However, the clay stabilizer has a large molecular weight and is easy to block low-permeability pores. The clay stabilizer has a higher positive charge content and is poorly compatible with anionic surfactants, anionic polymers and acid fracturing fluids used in the oil displacement process.
[0006] CN105198757A discloses a small cationic diquaternary ammonium salt clay stabilizer and a preparation method thereof. The clay stabilizer is prepared using epichlorohydrin, a small molecular tertiary amine and hydrochloric acid as raw materials. The clay stabilizer has a high positive charge density, good stability and clay swelling inhibition ability, but poor compatibility with anionic surfactants, anionic polymers and acid fracturing fluids used in the oil recovery process.
[0007] CN114716985A discloses a small cationic oligomeric anti-swelling quaternary ammonium salt clay stabilizer and a preparation method thereof. The small cationic oligomeric anti-swelling quaternary ammonium salt clay stabilizer is composed of a polyhydroxy quaternary ammonium salt aqueous solution and propylene oxide. The small cationic oligomeric anti-swelling quaternary ammonium salt clay stabilizer has the effects of preventing clay from absorbing water and swelling, bridging and binding clay particles, and preventing their migration. However, the clay stabilizer has a large molecular weight and is easy to block low-permeability pores, and has poor compatibility with anionic surfactants, anionic polymers and acid fracturing fluids used in the oil displacement process.
[0008] Therefore, it is urgent to develop a copolymer with multiple adsorption sites and an appropriate amount of positive charge. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of the copolymer in the prior art as a clay stabilizer, such as few adsorption points, poor compatibility, poor temperature resistance, poor anti-swelling performance and poor water washability, and to provide a copolymer and its preparation method and application and a clay stabilizer.
[0010] In order to achieve the above object, the first aspect of the present invention provides a copolymer, wherein the copolymer contains a structural unit A shown in formula I, a structural unit B shown in formula II and a structural unit C shown in formula III:
[0011]
[0012] Wherein, R is methyl and / or ethyl; and the molar ratio of structural unit A: structural unit B: structural unit C is (10-20):(60-350):(5-10).
[0013] A second aspect of the present invention provides a method for preparing a copolymer, wherein the method comprises:
[0014] In the presence of water and an initiator, the above-mentioned polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride are polymerized to obtain the copolymer; wherein the molar ratio of the polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride is (10-20):(60-350):(5-10).
[0015] The third aspect of the present invention provides a copolymer obtained by the above preparation method.
[0016] The fourth aspect of the present invention provides the use of the copolymer in oil field production and acid fracturing.
[0017] A fifth aspect of the present invention provides a clay stabilizer, the clay stabilizer comprising the above copolymer;
[0018] Preferably, in the clay stabilizer, the content of the copolymer is 0.5wt%-2wt%.
[0019] Through the above technical scheme, the copolymer provided by the present invention and its preparation method and application and clay stabilizer obtain the following beneficial effects:
[0020] (1) The copolymer provided by the present invention has a plurality of amine groups in its structural formula. As a clay stabilizer, it can not only be inserted into the lamellar structure of clay and embedded into the hexagonal ring formed by oxygen atoms, but also form multi-point adsorption; + The group makes its charge density moderate. On the one hand, it can "neutralize" the negative charge between clay crystal layers and on the clay surface, thereby reducing the repulsion between the crystal layers and particles, making the crystal layers shrink and not easy to hydrate; on the other hand, it can have good compatibility with anionic polymers, so that the clay stabilizer has excellent compatibility (compatibility with mud acid, fracturing fluid and anionic polymer is no stratification, precipitation and suspension), temperature resistance (temperature resistance can reach 350℃), anti-swelling performance (room temperature anti-swelling rate is 90.03-92.67% and 350℃ anti-swelling rate is 85.14-88.75%) and water washability (water washability is 95.01-98.50%); its molecular weight is moderate, so it will not cause blockage to low permeability formations;
[0021] (2) The method for preparing the copolymer provided by the present invention simplifies the operating conditions and process flow, and is convenient for industrial production. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The first aspect of the present invention provides a copolymer, wherein the copolymer contains a structural unit A represented by formula I, a structural unit B represented by formula II, and a structural unit C represented by formula III:
[0024]
[0025] Wherein, R is methyl and / or ethyl; and the molar ratio of structural unit A: structural unit B: structural unit C is (10-20):(60-350):(5-10).
[0026] In the present invention, the polymer contains multiple amine groups in its structural formula, which, as a clay stabilizer, can not only be inserted into the lamellar structure of clay and embedded into the hexagonal ring formed by oxygen atoms, but also form multi-point adsorption; + The group makes its charge density moderate. On the one hand, it can "neutralize" the negative charge between clay crystal layers and on the surface of clay, thereby reducing the repulsion between crystal layers and particles, making the crystal layers shrink and not easy to hydrate; on the other hand, it can have good compatibility with anionic polymers, so that the clay stabilizer has excellent compatibility, temperature resistance, anti-swelling performance and water washability; its molecular weight is moderate, so it will not cause blockage to low permeability formations.
[0027] According to the present invention, the viscosity average molecular weight of the copolymer is 5,000-30,000.
[0028] In the present invention, when the viscosity average molecular weight of the copolymer does not meet the above range, the molecular weight is too large, which is easy to block the formation pores and is not conducive to oil recovery in low permeability reservoirs; the molecular weight is too small, which cannot effectively prevent the migration of clay particles.
[0029] In the present invention, based on the total weight of the copolymer, the content of the compound of formula I is 10-25 wt% and the content of the compound of formula III is 5-10 wt%.
[0030] A second aspect of the present invention provides a method for preparing a copolymer, wherein the method comprises:
[0031] In the presence of water and an initiator, the above-mentioned polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride are polymerized to obtain the copolymer; wherein the molar ratio of the polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride is (10-20):(60-350):(5-10).
[0032] In the present invention, the concentration of the dimethyldiallylammonium chloride solution is 50-70wt%.
[0033] In the present invention, based on the total weight of polyamine acrylate, acrylamide and dimethyldiallylammonium chloride, the content of water is 149 wt % to 230 wt %.
[0034] In the present invention, nitrogen needs to be passed through at 30-50° C. for 30 minutes before the polymerization reaction.
[0035] According to the present invention, the preparation method of the polyamine acrylate comprises the following steps:
[0036] 1) in the presence of a water-carrying agent, a solid acid catalyst and a polymerization inhibitor, esterifying a polyol and acrylic acid to obtain a polyol acrylate;
[0037] 2) In the presence of tetrahydrofuran and Raney nickel catalyst, hydrogen and ammonia are introduced into the polyol acrylate to carry out a hydroamination reaction to obtain polyamine acrylate.
[0038] In the present invention, the esterification reaction conditions include: a time of 4-6 hours; satisfying the above esterification reaction conditions can ensure that polyol and acrylic acid are prepared into polyol acrylate, so as to ensure that the synthesized copolymer has excellent performance.
[0039] According to the present invention, the polyol acrylate is selected from di(aminomethyl)ethane acrylate and / or di(aminomethyl)propane acrylate.
[0040] According to the present invention, in step 1), the polyol is selected from tri(hydroxymethyl)ethane and / or tri(hydroxymethyl)propane.
[0041] According to the present invention, the water-carrying agent is selected from cyclohexane and / or toluene.
[0042] In the present invention, based on the total weight of the polyol and the acrylic acid, the content of the water-carrying agent is 128-180wt%.
[0043] According to the present invention, the solid acid catalyst is selected from zeolite molecular sieve and / or sulfonic acid type cation exchange resin.
[0044] According to the present invention, the polymerization inhibitor is selected from hydroquinone and / or 2-tert-butylhydroquinone.
[0045] According to the present invention, in step 1), the molar ratio of the polyol to acrylic acid is 1:(1-1.5).
[0046] According to the present invention, in step 1), based on the total weight of the polyol and acrylic acid, the content of the solid acid catalyst is 0.5wt%-1wt%, and the content of the polymerization inhibitor is 0.035wt%-0.05wt%.
[0047] In the present invention, when the polyol, acrylic acid, water-carrying agent, solid acid catalyst and polymerization inhibitor do not meet the above ranges, the synthesized polyamine has low purity and many by-products, which affects the next reaction and ultimately leads to poor copolymer performance.
[0048] According to the present invention, in step 2), the molar ratio of the polyol acrylate to ammonia is 1:(10-20), and the partial pressure of the hydrogen is 1.5 MPa-3 MPa.
[0049] According to the present invention, based on the total weight of the polyol acrylate and ammonia, the content of the Raney nickel catalyst is 1 wt%-3 wt%.
[0050] In the present invention, based on the total weight of the polyamine acrylate, the content of tetrahydrofuran is 473wt%-511wt%.
[0051] In the present invention, when the polyol acrylate, ammonia, hydrogen, tetrahydrofuran and Raney nickel catalyst do not meet the above ranges, the synthesized polyamine has low purity and many by-products, which affects the next reaction and ultimately leads to poor copolymer performance.
[0052] According to the present invention, the conditions of the hydroamination reaction include: temperature of 180-230° C. and time of 3-5 h.
[0053] According to the present invention, the mass ratio of ammonium persulfate to azobisisobutylamidine hydrochloride is (1.5-2):1.
[0054] In the present invention, the initiator is a mixture of ammonium persulfate, azobisisobutylamidine hydrochloride and water. Based on the total weight of polyamine acrylate, acrylamide and dimethyldiallylammonium chloride, the content of the initiator is 6wt%-13wt%; based on the total weight of the initiator, the content of ammonium persulfate and azobisisobutylamidine hydrochloride is 2.6wt%-6.5wt%; and the initiation temperature is 30-50°C.
[0055] According to the present invention, the polymerization reaction conditions include: temperature of 50-80° C. and time of 3-5 h.
[0056] The third aspect of the present invention provides a copolymer obtained by the above preparation method. The copolymer has the above properties and performance parameters, which will not be described in detail here.
[0057] The fourth aspect of the present invention provides the use of the copolymer in oil field production and acid fracturing.
[0058] A fifth aspect of the present invention provides a clay stabilizer, the clay stabilizer comprising the above copolymer;
[0059] Preferably, in the clay stabilizer, the content of the copolymer is 0.5wt%-2wt%.
[0060] The present invention will be described in detail below by way of examples. In the following examples,
[0061] The commercially available clay stabilizer model is FP-HJZ.
[0062] The raw materials used in the examples and comparative examples are all commercially available.
[0063] Example 1
[0064] 17.4 g of di(aminomethyl)ethane acrylate, 42.6 g of acrylamide, 13.41 g of 60 wt% dimethyldiallylammonium chloride and 110 g of deionized water were introduced into a nitrogen atmosphere at 50°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 80°C for 3 h, granulation, drying and pulverization were carried out to obtain copolymer A1, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.37 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.7:1, the viscosity-average molecular weight of A1 was 6,000, the content of formula I was 25 wt% and the content of formula III was 10 wt%.
[0065] Wherein, the preparation method of di(aminomethyl)ethane acrylate comprises:
[0066] 1) 30 g of tri(hydroxymethyl)ethane, 27 g of acrylic acid, 100 mL of cyclohexane, 0.57 g of zeolite molecular sieve and 0.027 g of hydroquinone were reacted for 4 h to obtain di(hydroxymethyl)ethane acrylate.
[0067] 2) 17.4 g of di(hydroxymethyl)ethane acrylate, 100 mL of tetrahydrofuran and 0.344 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 1.5 MPa of hydrogen was introduced, followed by 17 g of ammonia, and the mixture was reacted at 230° C. for 3 h to obtain di(aminomethyl)ethane acrylate.
[0068] Example 2
[0069] 18.8 g of di(aminomethyl)propane acrylate, 42.6 g of acrylamide, 13.41 g of 60 wt% dimethyldiallylammonium chloride and 170 g of deionized water were introduced with nitrogen at 30°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 50°C for 5 h, granulation, drying and pulverization were carried out to obtain copolymer A2, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.46 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.5:1, the viscosity-average molecular weight of A2 was 6,000, the content of formula I was 25 wt% and the content of formula III was 10 wt%.
[0070] Wherein, the preparation method of di(aminomethyl)propane acrylate comprises:
[0071] 1) 33.5 g of tri(hydroxymethyl)propane, 27 g of acrylic acid, 100 mL of cyclohexane, 0.605 g of zeolite molecular sieve and 0.027 g of hydroquinone were reacted for 4 h to obtain di(hydroxymethyl)propane acrylate;
[0072] 2) 18.8 g of di(hydroxymethyl)propane acrylate, 100 mL of tetrahydrofuran and 0.344 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 1.8 MPa of hydrogen was introduced, followed by 25.5 g of ammonia, and the mixture was reacted at 200° C. for 4 h to obtain di(aminomethyl)propane acrylate.
[0073] Example 3
[0074] 17.4 g of di(aminomethyl)ethane acrylate, 106.5 g of acrylamide, 13.41 g of 60 wt% dimethyldiallylammonium chloride and 200 g of deionized water were passed through nitrogen at 40°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 60°C for 4 h, granulation, drying and crushing were carried out to obtain copolymer A3, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.41 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 2:1, the viscosity-average molecular weight of A3 was 25,000, the content of formula I was 12 wt% and the content of formula III was 6 wt%.
[0075] Wherein, the preparation method of di(aminomethyl)ethane acrylate comprises:
[0076] 1) 30 g of tri(hydroxymethyl)ethane, 27 g of acrylic acid, 100 mL of toluene, 0.57 g of sulfonic acid type cation exchange resin and 0.027 g of hydroquinone were reacted for 5 h to obtain di(hydroxymethyl)ethane acrylate;
[0077] 2) 17.4 g of di(hydroxymethyl)ethane acrylate, 100 mL of tetrahydrofuran and 1.542 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 2 MPa of hydrogen was introduced, followed by 34 g of ammonia, and the reaction was carried out at 180° C. for 5 h to obtain di(aminomethyl)ethane acrylate.
[0078] Example 4
[0079] 18.8 g of di(aminomethyl)propane acrylate, 124.25 g of acrylamide, 13.41 g of 60 wt% dimethyldiallylammonium chloride and 300 g of deionized water were passed through nitrogen at 45°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 70°C for 3 h, granulation, drying and pulverization were carried out to obtain copolymer A4, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.35 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.5:1, the viscosity-average molecular weight of A4 was 30,000, the content of formula I was 10 wt% and the content of formula III was 5 wt%.
[0080] Wherein, the preparation method of di(aminomethyl)propane acrylate comprises:
[0081] 1) 33.5 g of tri(hydroxymethyl)propane, 27 g of acrylic acid, 100 mL of cyclohexane, 0.605 g of zeolite molecular sieve and 0.027 g of 2-tert-butylhydroquinone were reacted for 6 h to obtain di(hydroxymethyl)propane acrylate;
[0082] 2) 18.8 g of di(hydroxymethyl)propane acrylate, 100 mL of tetrahydrofuran and 0.741 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 1 MPa of hydrogen was introduced, followed by 30.6 g of ammonia, and the reaction was carried out at 210° C. for 3.5 h to obtain di(aminomethyl)propane acrylate.
[0083] Example 5
[0084] 17.4 g of di(aminomethyl)ethane acrylate, 94.67 g of acrylamide, 10.73 g of 60 wt% dimethyldiallylammonium chloride and 200 g of deionized water were introduced into a nitrogen atmosphere at 30°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 75°C for 5 h, granulation, drying and pulverization were carried out to obtain copolymer A5, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.49 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.8:1, the viscosity-average molecular weight of A5 was 18,000, the content of formula I was 13 wt% and the content of formula III was 5 wt%.
[0085] Wherein, the preparation method of di(aminomethyl)ethane acrylate comprises:
[0086] 1) 30 g of tri(hydroxymethyl)ethane, 23.4 g of acrylic acid, 100 mL of toluene, 0.534 g of zeolite molecular sieve and 0.0234 g of hydroquinone were reacted for 6 h to obtain di(hydroxymethyl)ethane acrylate;
[0087] 2) 17.4 g of di(hydroxymethyl)ethane acrylate, 100 mL of tetrahydrofuran and 1.338 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 2.5 MPa of hydrogen was introduced, followed by 27.2 g of ammonia, and the reaction was carried out at 220° C. for 4 h to obtain di(aminomethyl)ethane acrylate.
[0088] Example 6
[0089] 17.4 g of di(aminomethyl)ethane acrylate, 94.67 g of acrylamide, 14.31 g of 60 wt% dimethyldiallylammonium chloride and 200 g of deionized water were introduced into a nitrogen atmosphere at 50°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 65°C for 4.5 h, granulation, drying and pulverization were carried out to obtain copolymer A6, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.505 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.6:1, the viscosity-average molecular weight of A6 was 17,000, the content of formula I was 14 wt% and the content of formula III was 7 wt%.
[0090] Wherein, the preparation method of di(aminomethyl)ethane acrylate comprises:
[0091] 1) 30 g of tri(hydroxymethyl)ethane, 18 g of acrylic acid, 100 mL of toluene, 0.48 g of zeolite molecular sieve and 0.018 g of hydroquinone were reacted for 5.5 h to obtain di(hydroxymethyl)ethane acrylate;
[0092] 2) 17.4 g of di(hydroxymethyl)ethane acrylate, 100 mL of tetrahydrofuran and 1.258 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 3 MPa of hydrogen was introduced, followed by 34 g of ammonia, and the mixture was reacted at 200° C. for 5 h to obtain di(aminomethyl)ethane acrylate.
[0093] Example 7
[0094] 18.8 g of di(aminomethyl)propane acrylate, 71 g of acrylamide, 12.52 g of 60 wt% dimethyldiallylammonium chloride and 230 g of deionized water were introduced into a nitrogen atmosphere at 30°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 50°C for 3.5 h, granulation, drying and pulverization were performed to obtain copolymer A7, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.65 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.5:1, the viscosity-average molecular weight of A7 was 14,000, the content of formula I was 19 wt% and the content of formula III was 7 wt%.
[0095] Wherein, the preparation method of di(aminomethyl)propane acrylate comprises:
[0096] 1) 33.5 g of tri(hydroxymethyl)propane, 27 g of acrylic acid, 100 mL of cyclohexane, 0.605 g of sulfonic acid type cation exchange resin and 0.027 g of 2-tert-butylhydroquinone were reacted for 4 h to obtain di(hydroxymethyl)propane acrylate;
[0097] 2) 18.8 g of di(hydroxymethyl)propane acrylate, 100 mL of tetrahydrofuran and 1.96 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 3 MPa of hydrogen was introduced, followed by 20.4 g of ammonia, and the reaction was carried out at 230° C. for 4 h to obtain di(aminomethyl)propane acrylate.
[0098] Example 8
[0099] 18.8 g of di(aminomethyl)propane acrylate, 76.1 g of acrylamide, 19.16 g of 60 wt% dimethyldiallylammonium chloride and 260 g of deionized water were introduced with nitrogen at 45°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 80°C for 3 h, granulation, drying and crushing were carried out to obtain copolymer A8, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.63 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 2:1, the viscosity-average molecular weight of A8 was 14,000, the content of formula I was 17 wt% and the content of formula III was 10 wt%.
[0100] Wherein, the preparation method of di(aminomethyl)propane acrylate comprises:
[0101] 1) 33.5 g of tri(hydroxymethyl)propane, 21.6 g of acrylic acid, 100 mL of cyclohexane, 0.511 g of zeolite molecular sieve and 0.0216 g of hydroquinone were reacted for 4.5 h to obtain di(hydroxymethyl)propane acrylate;
[0102] 2) 18.8 g of di(hydroxymethyl)propane acrylate, 100 mL of tetrahydrofuran and 1.32 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 2 MPa of hydrogen was introduced, followed by 34 g of ammonia, and the reaction was carried out at 230° C. for 3.5 h to obtain di(aminomethyl)propane acrylate.
[0103] Example 9
[0104] 17.4 g of di(aminomethyl)ethane acrylate, 41.76 g of acrylamide, 14.21 g of 60 wt% dimethyldiallylammonium chloride and 110 g of deionized water were introduced into a nitrogen atmosphere at 35°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 55°C for 4 h, granulation, drying and pulverization were carried out to obtain copolymer A9, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.26 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 2:1, the viscosity-average molecular weight of A9 was 11,000, the content of formula I was 25 wt% and the content of formula III was 12 wt%.
[0105] Wherein, the preparation method of di(aminomethyl)ethane acrylate comprises:
[0106] 1) 30 g of tri(hydroxymethyl)ethane, 21.6 g of acrylic acid, 100 mL of toluene, 0.516 g of zeolite molecular sieve and 0.0216 g of hydroquinone were reacted for 5 h to obtain di(hydroxymethyl)ethane acrylate;
[0107] 2) 17.4 g of di(hydroxymethyl)ethane acrylate, 100 mL of tetrahydrofuran and 1.338 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 2.5 MPa of hydrogen was introduced, followed by 27.2 g of ammonia, and the reaction was carried out at 180° C. for 4.5 h to obtain di(aminomethyl)ethane acrylate.
[0108] Example 10
[0109] 18.8 g of di(aminomethyl)propane acrylate, 98.61 g of acrylamide, 13.41 g of 60 wt% dimethyldiallylammonium chloride and 300 g of deionized water were passed through nitrogen at 35°C for 30 min, 10 g of initiator was added, polymerization reaction was carried out at 70°C for 3.5 h, granulation, drying and crushing were carried out to obtain copolymer A10, wherein the total mass of ammonium sulfate and azobisisobutyramidine hydrochloride in the initiator was 0.33 g, the mass ratio of ammonium sulfate to azobisisobutyramidine hydrochloride was 1.5:1, the viscosity-average molecular weight of A10 was 22,000, the content of formula I was 14 wt% and the content of formula III was 5 wt%.
[0110] Wherein, the preparation method of di(aminomethyl)propane acrylate comprises:
[0111] 1) 33.5 g of tri(hydroxymethyl)propane, 25.2 g of acrylic acid, 100 mL of toluene, 0.587 g of sulfonic acid type cation exchange resin and 0.0252 g of 2-tert-butylhydroquinone were reacted for 6 h to obtain di(hydroxymethyl)propane acrylate;
[0112] 2) 18.8 g of di(hydroxymethyl)propane acrylate, 100 mL of tetrahydrofuran and 1.278 g of Raney nickel catalyst were added to a reaction kettle, and the atmosphere was replaced with nitrogen twice and hydrogen twice, and then 1.8 MPa of hydrogen was introduced, followed by 23.8 g of ammonia, and the mixture was reacted at 220° C. for 4 h to obtain di(aminomethyl)propane acrylate.
[0113] Comparative Example 1
[0114] The method of Example 1 was followed, except that the mass of dimethyldiallylammonium chloride was replaced by 30 g, to obtain copolymer D1.
[0115] Comparative Example 2
[0116] The method of Example 1 was followed, except that the mass of di(aminomethyl)propane acrylate was changed to 5 g, to obtain copolymer D2.
[0117] Comparative Example 3
[0118] The method of Example 1 was followed, except that dimethyldiallylammonium chloride was replaced with acryloyloxyethyltrimethylammonium chloride, to obtain copolymer D3.
[0119] Test Example 1
[0120] The copolymers prepared in the examples and comparative examples and commercially available samples were subjected to performance tests.
[0121] The anti-swelling rate and water washability at room temperature are measured according to SY / T5971-2016;
[0122] The anti-swelling rate at 350°C is measured by the following method:
[0123] Add 3g of sodium bentonite to 60mL of 1wt% copolymer solution, shake well and mix, then put it into an aging kettle; then put it into a high-temperature aging furnace and age it at 350℃ for 24h; after cooling to room temperature, transfer all the copolymer solution in the aging kettle into a 100mL beaker, shake well, quickly take out 10mL and add it to a centrifuge tube, put it into a centrifuge with automatic balancing function, centrifuge it at 1500r / min for 15min, and read the expansion volume V1 of the bentonite. The high-temperature anti-swelling rate calculation formula is as follows:
[0124]
[0125] Where: F—high temperature anti-expansion rate, %;
[0126] V0—volume of sodium bentonite in kerosene, mL;
[0127] V1—volume of sodium bentonite in clay stabilizer, mL;
[0128] V2—Volume of sodium bentonite in clean water, mL.
[0129] Table 1
[0130] Anti-swelling rate at room temperature, % 350℃ anti-swelling rate, % Washing resistance, % A1 92.00 86.31 98.15 A2 92.67 86.72 98.50 A3 90.67 85.14 96.82 A4 90.03 85.21 95.01 A5 90.13 86.01 95.36 A6 91.33 86.52 96.94 A7 91.47 86.39 97.87 A8 91.60 87.01 96.71 A9 91.87 88.75 97.36 A10 91.73 86.12 95.13 D1 90.02 85.01 95.31 D2 80.36 76.23 87.21 D3 86.32 61.02 88.17 Commercially available samples 61.82 40.86 82.21
[0131] It can be seen from Table 1 that the copolymer prepared in the present invention has good anti-swelling performance, temperature resistance and water washing resistance.
[0132] Test Example 2
[0133] The compatibility test of the copolymer was carried out according to Q / SH 0053-2010. The test results are shown in Table 2.
[0134] Table 2
[0135]
[0136] It can be seen from Table 2 that the copolymer prepared in the present invention has good compatibility with acid solution, fracturing fluid and anionic polymer solution.
[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copolymer, characterized in that The copolymer contains a structural unit A shown in formula I, a structural unit B shown in formula II, and a structural unit C shown in formula III: Wherein, R is methyl and / or ethyl; and the molar ratio of structural unit A: structural unit B: structural unit C is (10-20):(60-350):(5-10).
2. The copolymer according to claim 1, wherein The viscosity average molecular weight of the copolymer is 5,000-30,000.
3. A method for preparing a copolymer, characterized in that: The method comprises: In the presence of water and an initiator, polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride are polymerized to obtain the copolymer; wherein the molar ratio of polyamine acrylate, acrylamide and dimethyldiallyl ammonium chloride is (10-20):(60-350):(5-10).
4. The preparation method according to claim 3, wherein The preparation method of the polyamine acrylate comprises the following steps: 1) in the presence of a water-carrying agent, a solid acid catalyst and a polymerization inhibitor, esterifying a polyol and acrylic acid to obtain a polyol acrylate; 2) in the presence of tetrahydrofuran and Raney nickel catalyst, introducing hydrogen and ammonia into the polyol acrylate to carry out a hydroamination reaction to obtain a polyamine acrylate; Preferably, the polyol acrylate is selected from di(aminomethyl)ethane acrylate and / or di(aminomethyl)propane acrylate.
5. The preparation method according to claim 4, wherein: In step 1), the polyol is selected from tri(hydroxymethyl)ethane and / or tri(hydroxymethyl)propane; Preferably, the water-carrying agent is selected from cyclohexane and / or toluene; Preferably, the solid acid catalyst is selected from zeolite molecular sieve and / or sulfonic acid type cation exchange resin; Preferably, the polymerization inhibitor is selected from hydroquinone and / or 2-tert-butylhydroquinone.
6. The preparation method according to claim 4 or 5, wherein: In step 1), the molar ratio of the polyol to acrylic acid is 1:(1-1.5); Preferably, based on the total weight of the polyol and acrylic acid, the content of the solid acid catalyst is 0.5 wt%-1 wt%, and the content of the polymerization inhibitor is 0.035 wt%-0.05 wt%.
7. The preparation method according to any one of claims 4 to 6, wherein: In step 2), the molar ratio of the polyol acrylate to ammonia is 1:(10-20), and the partial pressure of the hydrogen is 1.5 MPa-3 MPa; Preferably, based on the total weight of the polyol acrylate and ammonia, the content of the Raney nickel catalyst is 1wt%-3wt%; Preferably, the conditions of the hydroamination reaction include: temperature of 180-230° C. and time of 3-5 h.
8. The preparation method according to any one of claims 3 to 7, wherein: The initiator is a mixture of ammonium persulfate, azobisisobutyramidine hydrochloride and water; Preferably, the mass ratio of ammonium persulfate to azobisisobutylamidine hydrochloride is (1.5-2):1; Preferably, the polymerization reaction conditions include: temperature of 50-80° C. and time of 3-5 h.
9. A copolymer obtained by the preparation method according to any one of claims 3 to 8.
10. Use of the copolymer according to any one of claims 1 or 2 and 9 in oil field oil production and acid fracturing.
11. A clay stabilizer, characterized in that: The clay stabilizer comprises the copolymer according to any one of claims 1, 2 and 9; Preferably, in the clay stabilizer, the content of the copolymer is 0.5wt%-2wt%.
Citation Information
Patent Citations
Small cationic bisquaternary ammonium salt clay stabilizer and preparation method thereof
CN105198757A
Clay anti-swelling agent solution and preparation method thereof
CN115232016A